Preparation and characterization studies of pure and Li+ doped ZnO nanoparticles for optoelectronic applications. (2021) - Chandrasekar, M.; Panimalar, S.; Uthrakumar, R.; Kumar, M.; Raja Saravanan, M.E.; Gobi, G.; Matheswaran, P.; Inmozhi, C.; Kaviyarasu, K.
Abstract: In this present work, the synthesis of pure and Li doped zinc oxide nanoparticles by hydrothermal method using zinc nitrate and sodium hydroxide synthesized and has been reported. CTAB added in nanoparticles preparation, where CTAB used as the size reducing reagent, is one of the most essential properties for the nanoparticle's preparation and its characterisation. The synthesized zinc oxide nanoparticles were characterized by X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) Spectroscopy and UV Visible Spectroscopy (UV–vis) were reported in detail.